IRMPD spectroscopy and QC calculations on functionalized gold nanocluster ions. Issue 20 (January 2020) - Desfrançois, C; Beydoun, A; Lecomte, F; Nieuwjaer, N; Manil, B; Scuderi, D
Synopsis: Many studies are devoted to functionalized metallic nanoparticles, for many applications: in Physics, due to their localized surface plasmon resonances; in Chemistry, due to their specific catalytic properties that depend on their surface nature; in Biology, due to their optical or magnetic properties coupled to their potential for targeting and vectorization of bioactive molecules within living cells. In this last domain, gold and silver nanoparticles are especially of interest and, for the control of their biological effects, it is very important to have a fine knowledge of the structural properties and the chemical stabilities of their functional ligands.